2013
DOI: 10.2147/opth.s32177
|View full text |Cite
|
Sign up to set email alerts
|

Profile of verteporfin and its potential for the treatment of central serous chorioretinopathy

Abstract: Central serous chorioretinopathy (CSCR) is an idiopathic disorder characterized by serous retinal detachments associated with focal leakage on fluorescein angiography and pigment epithelial detachments. While the majority of cases improve spontaneously over several months, a significant subset of patients advance to a chronic recurrent form of the disease with diffuse pigment epitheliopathy, foveal atrophy, scarring, and permanent visual loss. Photodynamic therapy (PDT) with verteporfn has been extensively stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…A variety of photosensitisers have been investigated for the generation of singlet oxygen, including rose bengal, fluorescein, porphyrin, and phthalocyanine 42 46 47 . Because of their high singlet-oxygen quantum yield and strong visible-light absorption ability, the most widely used photosensitisers are porphyrin derivatives and some of these derivatives have been commercialised for photodynamic therapy (i.e., Foscan 48 , Laser-phyrin 49 , Photofrin 50 , and Visudyne 51 ). However, the production of ideal photosensitisers for photodynamic therapy with a much greater efficiency and light-harvesting capacity in the long-wavelength region remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of photosensitisers have been investigated for the generation of singlet oxygen, including rose bengal, fluorescein, porphyrin, and phthalocyanine 42 46 47 . Because of their high singlet-oxygen quantum yield and strong visible-light absorption ability, the most widely used photosensitisers are porphyrin derivatives and some of these derivatives have been commercialised for photodynamic therapy (i.e., Foscan 48 , Laser-phyrin 49 , Photofrin 50 , and Visudyne 51 ). However, the production of ideal photosensitisers for photodynamic therapy with a much greater efficiency and light-harvesting capacity in the long-wavelength region remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…While verteporfin has been shown to be a good YAP inhibitor in previous studies on NSCLC, its use has been limited to preclinical models [ 158 , 159 , 160 , 161 ]. In fact, verteporfin is only optimized for photodynamic therapy to treat vascular disorders of the eyes and is not designed for clinical anticancer therapy [ 162 , 163 ]. A recent study showed that the reactivation of YAP promotes survival and dormancy in EGFR mutant NSCLC cells, while EGFR downstream signaling is suppressed by EGFR and MEK inhibitors [ 98 ].…”
Section: Future Perspectives: Potential Therapies Targeting Src–yamentioning
confidence: 99%
“…Whereas observation is the appropriate first-line approach for acute episodes, 6 long-standing subretinal detachments may induce irreversible photoreceptor damage, and treatment is therefore justified in these cases. 7 …”
Section: Introductionmentioning
confidence: 99%